2021
DOI: 10.1001/jamanetworkopen.2021.41321
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes After Statin Exposure During Pregnancy

Abstract: IMPORTANCEStatins are the drug class most commonly used to treat hyperlipidemia. Recently, they have been used during pregnancy for the prevention or treatment of preeclampsia. However, the safety of statin use during pregnancy has been questioned, and the sample sizes of most previous studies have been small. OBJECTIVE To examine the perinatal outcomes among offspring associated with maternal use of statins during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…Also, despite the high number of pregnancies (n = 822 071), in relatively few pregnancies (n = 298, 0.036 %), a prescription for a statin had been filled during first trimester. This is largely in line with data from other populations [1519]. Although reassuring, the low frequency of statin exposure during pregnancy limits the power of drug safety analyses.…”
Section: Discussionsupporting
confidence: 77%
“…Also, despite the high number of pregnancies (n = 822 071), in relatively few pregnancies (n = 298, 0.036 %), a prescription for a statin had been filled during first trimester. This is largely in line with data from other populations [1519]. Although reassuring, the low frequency of statin exposure during pregnancy limits the power of drug safety analyses.…”
Section: Discussionsupporting
confidence: 77%
“…The studies were published between 2007 and 2021 and originated from the United States ( n = 4), Canada ( n = 2), United Kingdom ( n = 2), Indonesia ( n = 1), Greece ( n = 1), Taiwan ( n = 1) and multicentre over Europe ( n = 1). Four studies were RCT’s ( Costantine et al, 2016 ; Ahmed et al, 2020 ; Deviana et al, 2020 ), ( Costantine et al, 2021 ) and eight studies were cohort studies ( Lefkou et al, 2016 ; McGrogan et al, 2017 ; Lee et al, 2018 ; Chang et al, 2021 ; Winterfeld et al, 2013 ), ( Taguchi et al, 2008 ; Bateman et al, 2015 ), ( Ofori et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis of 9 observational studies found no association between statin use and stillbirth (OR 1.30; 95% CI 0.56-3.0; p=0.54), induced abortion (OR 2.08; 95% CI; 0.81-5.36; p=0.129), or elective abortion (OR 1.37; 95% CI, 0.68-2.76; p=0.378) [5] but spontaneous abortion was more common (OR 1.36; 95% CI, 1.10-1.68; p=0.004). More recently, a retrospective cohort study of 469 statin-exposed pregnant women (vs. 4,690 matched controls) reported no increase in congenital anomalies (RR, 1.24; 95% CI 0.81-1.90 after adjustment for maternal age and comorbidities), although there was a greater risk of low birth weight (RR 1.51; 95% CI, 1.05-2.16) and preterm birth (RR 1.99; 95% CI, 1.46-2.71) [16].…”
mentioning
confidence: 92%
“…The apparently lower risk with hydrophilic statins may be due to a lower tendency to cross the placenta [17]. Unexpectedly, adverse neonatal outcomes were less likely in a subgroup of 174 women who continued statins throughout pregnancy compared to 395 women who discontinued statins after conception was confirmed [16].…”
mentioning
confidence: 98%
See 1 more Smart Citation